2009
DOI: 10.1159/000167861
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Gastric Emptying Disorders in Patients with Functional Dyspepsia Reveals Impaired Inhibitory Gastric Emptying Regulation in the Early Postcibal Period

Abstract: Background/Aims: The aim of the study was to investigate gastric emptying profiles in patients with postprandial distress syndrome (PDS) as a means to understand relationships between gastric emptying and dyspepsia. Methods: Gastric emptying times were measured using a 13C breath test. In addition to comparisons of 13C half excretion times (t 1/2 ex) between patients with PDS and healthy subjects, gastric emptying (%dose/h) curves were analyzed using a multipeak curve-fitting technique, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 41 publications
(23 reference statements)
1
27
0
Order By: Relevance
“…early postprandial period or impaired inhibitory gastric emptying in the mid postprandial period supporting the observation that functional dyspepsia is a heterogeneous disorder [Zai and Kusano, 2009].…”
Section: Gastric Emptying Studiessupporting
confidence: 70%
“…early postprandial period or impaired inhibitory gastric emptying in the mid postprandial period supporting the observation that functional dyspepsia is a heterogeneous disorder [Zai and Kusano, 2009].…”
Section: Gastric Emptying Studiessupporting
confidence: 70%
“…Analyses of dysregulation of early phase of gastric emptying are necessary to elucidate the pathphysiology of FD patients. 29 Accelerated gastric emptying in the early postprandial period may be associated with impaired accommodation. 39,40 In addition, in a scintigraphic study, early redistribution of the meal to the distal stomach or accelerated gastric emptying in the postprandial period, suggestive of impaired accommodation, was associated with symptoms of early satiety.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the large capacity of the stomach in persons with gastroptosis might mean that a larger volume is needed to trigger TLESR than in persons with a normal stomach or cascade stomach. Recently, early gastric emptying has been suggested to have an important role in the development of dyspepsia (13)(14)(15), rather than delayed gastric emptying (3,4,16). It was reported that patients with severe nausea and vomiting have very rapid emptying of swallowed barium during fluoroscopy (17).…”
Section: Discussionmentioning
confidence: 99%